Competition in Soccer Leagues - Mich Tvede; Bodil Olai Hansen (Copenhagen Business School (CBS), Department of Economics, 2007)
In the present paper a model of competition between sports clubs in a sports league is presented. Clubs are endowed with initial players but at a cost clubs are able to sell their initial players and buy new players. The results are that: if the quality of players is one-dimensional, then equilibria in pure strategies exist, and; if the quality of players is multi-dimensional, then there need not exist equilibria in pure strategies, but equilibria in mixed strategies exist. Equilibria in mixed strategies resemblance signings just before the transfer window closes in european soccer. competition between sports clubs, dimension of quality of players, equilibrium in pure strategies, equilibrium in mixed strategies.
hdl:10398/7555
Keywords: 330